Attitudes of nurses and nursing students towards patients with mental illness - Srdjan Živanović; Veselinka Kulić; Bojan Joksimović; Vedrana Joksimović; Marija Milić (Биомедицинска истраживања, 2022)
Introduction: . According to the data of the World Health Organization (WHO), mental illnesses are on the rise. The World Health Report es timates that today about 1 billion people suffer from mental and be havioral disorders or psychosocial problems such as those related to alcohol and drug abuse. Stigmatization of the mentally ill is one of the burning social problems of those people, and the attitudes and behav ior of nurses/technicians significantly affect the self-stigmatization of patients, and thus their condition and recovery. The main aim of this study was to assess attitudes of nurses and nursing students towards patients with mental illnesses. Method: . The research conducted is a cross-sectional study. The study cov ered two countries, Bosnia and Herzegovina and Serbia. In June and July 2018, 200 nurses and nursing students from the second to the fourth year of study were surveyed. Data were collected with original anonymous questionnaires, which was made for the purpose of this research. Results: . Seventy percent of nurses believe that people with mental illness are discriminated against in our society, while there are statisti cally significant differences between respondents in relation to demo graphic characteristics (χ2 = 10.217; p = 0.037). Nurses working in psy chiatric wards show a lower level of stigmatization compared to nurs es working in other wards (χ2 = 25.553; p = 0.001). Nursing students have more negative attitudes towards mentally ill people compared to nurses (χ2 = 13.471; p = 0.009). Nurses from Serbia show a higher level of tolerance towards people with mental disabilities compared to nurses from Bosnia and Herzegovina (χ2 = 16.115; p = 0.003). Conclusion: . The results of the research show that stigmatization of patients with mental illness still exists among health professionals. Undergraduate and continuing medical education of nurses should include more content related to access to the patient with mental dis orders, communication skills in psychiatry, mental health promotion and prevention of stigmatization.
Keywords: stigma; nurses; mental illness